2020
DOI: 10.1136/bmjopen-2020-036903
|View full text |Cite
|
Sign up to set email alerts
|

Foot health and quality of life in patients with rheumatoid arthritis: a cross-sectional study

Abstract: ObjectiveThe aim of this study is to identify foot health factors related to the quality of life in patients with rheumatoid arthritis (RA).SettingIn this cross-sectional study, a total of 293 subjects were analysed, 229 of whom were in the RA group and 64 in the control group. In the RA group, 173 patients were female, and 50 in the control group.ParticipantsPatients with foot pain and RA (according to the American College of Rheumatology/European League Against Rheumatism 2010 rheumatoid arthritis classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
4
14
1
Order By: Relevance
“…In other words, in the control group, the left and right feet were morphologically and structurally equivalent. Thus, although the symmetric involvement of the joints is often considered a characteristic feature of RA [ 4 , 9 , 10 , 11 , 12 ], this association is not confirmed by our study findings.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…In other words, in the control group, the left and right feet were morphologically and structurally equivalent. Thus, although the symmetric involvement of the joints is often considered a characteristic feature of RA [ 4 , 9 , 10 , 11 , 12 ], this association is not confirmed by our study findings.…”
Section: Discussioncontrasting
confidence: 97%
“…According to most authors, the joint damage provoked by RA is largely symmetric, and the first symptoms are considered to be symmetric polyarthritis of the small joints, together with pain, inflammation, and stiffness of the hand and/or foot. However, although symmetry is often said to be a prominent feature of RA [ 4 , 9 , 10 , 11 , 12 ], there is no scientific evidence to support this view. In this respect, Zangger et al reported a general prevalence of asymmetry in joint damage in RA (of approximately 13–16%) and a tendency for this asymmetry to increase slightly as the disease progresses [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Poland RA affects approximately 1% of the adult population, which is around 400,000 individuals [ 19 , 20 ]. Recent medical studies reflect an increased interest in health-related quality of life of patients, particularly those with chronic diseases [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the Manchester Spanish [MFPDI] questionnaire was also employed with the F-F-I in a population of arthritis patients linked with healthy patients with significant differences, especially with a VAS of 6 to 2 for arthritis patients with foot pain vs. arthritis foot patients without foot pain, in the research of Reinoso-Cobo et al [ 32 ].…”
Section: Discussionmentioning
confidence: 99%